2015
DOI: 10.1038/icb.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan hydrogel vaccine generates protective CD8 T cell memory against mouse melanoma

Abstract: CD8(+) T cells are important in the control of viral infections and cancers because of their cytolytic activity. A vaccine able to generate these cells could be beneficial in the prevention or treatment of these diseases. Chitosan hydrogel is a promising vaccine formulation that has previously been shown to generate effector CD8(+) T cells in a mouse model. This vaccine promotes sustained release of antigen and adjuvant, which generates a robust effector response. For longer lasting immunity, a memory populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 48 publications
6
31
0
Order By: Relevance
“…The pentablock copolymer hydrogels with their increased stability and sustained release of antigen and immunomodulators stimulated strong, long-lasting T cell and antibody responses. These results are in agreement with the recent investigations on chitosan thermoresponsive hydrogels as sustained vaccine delivery systems; however, those systems had less than optimal formulation characteristics (36,43). Interestingly, the inclusion of PLGA-NP in the hydrogels delayed the induction of both cellular and humoral immune responses, possibly due to the reduced burst release and overall slower release of vaccine components.…”
Section: Discussionsupporting
confidence: 81%
“…The pentablock copolymer hydrogels with their increased stability and sustained release of antigen and immunomodulators stimulated strong, long-lasting T cell and antibody responses. These results are in agreement with the recent investigations on chitosan thermoresponsive hydrogels as sustained vaccine delivery systems; however, those systems had less than optimal formulation characteristics (36,43). Interestingly, the inclusion of PLGA-NP in the hydrogels delayed the induction of both cellular and humoral immune responses, possibly due to the reduced burst release and overall slower release of vaccine components.…”
Section: Discussionsupporting
confidence: 81%
“…Chitosan was selected as the polymer core of the particulate vaccines due to its inherent immunostimulatory properties (Highton et al, 2015;Zaharoff et al, 2007;Zhu et al, 2007), which is thought to be mediated through engagement of TLR4 and mannose receptors on antigen-presenting cells (Villiers et al, 2009). Rather unexpectedly, the results of the in vitro evaluation of our chitosan particles showed that non-adjuvanted particles failed to induce cytokine responses from porcine DCs and elicited only an IL-8 response from monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan hydrogels are a sustained-release vaccine delivery system, primarily consisting of the naturally occurring polymer chitosan [26]. Chitosan solutions can be altered by the addition of polyol salts to be thermosensitive, such that the hydrogels are only formed at body temperature.…”
Section: Hydrogel Capsulesmentioning
confidence: 99%